Platelets contribute to growth and metastasis in hepatocellular carcinoma. Issue 9 (25th July 2016) - Bihari, Chhagan; Rastogi, Archana; Shasthry, Saggere Muralikrishna; Bajpai, Meenu; Bhadoria, Ajeet Singh; Rajesh, S.; Mukund, Amar; Kumar, Anupam; Sarin, Shiv K.
Abstract : To determine the association of platelets with hepatocellular carcinoma (HCC) growth and its metastasis. We examined platelets, laboratory, and radiological data of consecutive 420 HCC and 1008 cirrhosis cases. Follow‐up information of platelet count in cirrhosis to HCC, pre‐ to post‐therapy, and post‐therapy to HCC outcome was analyzed. Cytokine profiling was performed in HCC and cirrhosis ( n = 10 each). On the basis of imaging, HCC was divided into six subgroups. Cytosmears of HCC were assessed for platelet clustering around tumor cells. An in vitro Matrigel invasion assay was performed on human HCC cell lines using graded concentration of platelets. Baseline platelet numbers and platelet/lymphocyte ratios (PLRs) were significantly higher (p < 0.001) in HCC than cirrhosis. IL‐1, IL‐6, FGF, G‐CSF, thrombopoietin, and VEGF were higher in HCC than cirrhosis. Platelet counts were increased after HCC conversion of cirrhosis (p < 0.001) and decreased (p < 0.001) after therapy. Platelets and PLR in recurrence cases were higher than in responders at baseline. AFP, PIVKAII, platelets, and PLR increase (p < 0.001 each) with advancement in HCC growth. Multivariate analysis showed platelets (p = 0.002), PLR (p = 0.004), and AFP (p < 0.001) associated with distant metastasis. Platelet clustering seen in 75.7% of HCC group 3, 45% in group 2, and 12.5% in group 1 cases (p < 0.001). Invaded cells in Matrigel assay positively correlated with platelet concentration. Platelets can contribute to the development, growth, invasion, and metastasis of HCC. Rising platelet count after HCC therapy is indicative of incomplete response or recurrence.